(untitled) (Canadian Medical Education Journal, 2024)
Background: Teamwork in healthcare is shaped by reciprocal interactions among individual team members and their clinical context. Cultural Historical Activity Theory (CHAT) provides a framework to study teamwork from a developmental perspective. We observed interactions between members of an Interprofessional Healthcare Team (IHT) to identify practical guidelines for educators. Method: Three Health Care Providers (HCPs) with more than 22-years’ experience in a semi-urban LTC facility participated. We video-recorded two regular IHT meetings and selected excerpts for subsequent video-recall interviews. The excerpts were shown and discussed first with each team member, then with members in pairs and finally with all members reunited. We prompted participants to explain what was happening on the videos. All interviews were recorded, transcribed, and analyzed using CHAT’s unit of analysis based on Activity Systems. Findings: We observed contradictions within the Activity Systems involving diverging views on outcomes of enhancing or maintaining quality of life; using non-traditional tools and spaces to sustain resident mobility; safeguarding community and patient safety despite time constraints and job titles, and unease for being paid to perform unconventional interventions. The contradictions have been grouped into three themes reflecting the Activity Systems: 1) enhancing versus maintaining quality of life; 2) improvising to achieve care goals; and 3) role fluidity. Discussion: Our findings show that practical goal-oriented and contextual adaptations rely heavily on improvisation and dialogue. Educating HCPs for interprofessional teamwork should focus on developing situational awareness to foster continuous adaptation of disciplinary interventions.